Kazıklı kıyı yapılarının doğrusal olmayan davranışı ve şekil değiştirmeye göre tasarımı - Kadıoğlu, Ziya (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2015)
Uluslararası ticaretin önemli bir ayağı olan limanlar ulaşım ağında önemli bir yer tutar. Bu liman yapılarının işlevlerindeki herhangi bir kesinti büyük kayıplara yol açabilir. Çoğu limanlar orta-yüksek deprem tehlikesine sahip bölgelerde yer almaktadır. Kıyı yapılarında dolgulardaki sıvılaşma ve yanal yayılmaya bağlı geçmiş 1995 Kobe ve 2010 Haiti depremlerinde, yapısal ve yapısal olmayan önemli hasarlar gözlenmiştir. Özellikle sismik bölgelerde kıyı ve liman yapılarında depreme dayanıklı tasarım ve uygulamanın önemi büyüktür. Bu çalışmada, İzmit körfezinde yer alan bir kazıklı rıhtım yapısı seçilmiştir. Ele alınan yapının önce yapısal modeli oluşturulmuş, bu model ile lineer olmayan itme analizi gerçekleştirilmiştir. Hipotetik olarak mevcut eğik çelik kazıkların eğim açıları değiştirilmiş ve bu değişikliklerin modelin genel davranışına olan etkileri araştırılmıştır.

Serving as critical gateways for international trade seaports are essential elements in transportation networks. Any disruption in the activities of port structure may lead significant losses. Many of ports are located in seismic zones subjected to moderate to high seismic hazards. Critical damages have been experienced during past earthquakes such as 1995 Kobe Earthquake and 2010 Haiti Earthquake in which liquefaction and lateral spreading of embankments imposed severe damage to both structural and non-structural components of port structures. Hence it is important that port and wharf structures should adequately be designed and built in seismic zones. In this study, pile supported wharf structure located at İzmit Bay is selected to be modeled. Nonlinear static (push-over) analysis for the seismic performance evaluation has been carried out on structure model. As hypothetically, four different incline angles 0, 15, 30, 45, respectively of steel piles are used inside the model. The effects of angle changes and inferences on the seismic response of model are investigated.
Deformation based design and nonlinear behavior of pile supported wharf structures
Keywords: İnşaat Mühendisliği; Civil Engineering